Crisis Communication Strategies in Addressing Internal Conflicts Among Scout Members at State Junior High School 3 Losari Department of Communication Studies Faculty of Social and Political Sciences - Adhnen Eghy Dermawan; Farida Nurfalah; Abdul Jalil Hermawan (Journal of World Science, 2026)
The school setting plays a key role in shaping students' character and leadership through scouting activities; however, internal dynamics can lead to conflicts that may escalate into crises, making effective conflict management and communication essential for maintaining organizational reputation. This study examines the internal issues and communication tactics of the scouting organization at State Junior High School 3 Losari, and explores how these factors shape the organization's image. A qualitative descriptive approach was employed, with data gathered through in-depth interviews, observation, and document analysis, then analyzed using Coombs' Situational Crisis Communication Theory (SCCT). The findings reveal that unequal distribution of responsibilities, communication breakdowns, and differing perspectives are the primary sources of internal conflict, which are addressed through crisis communication mechanisms including denial, consequence mitigation, relationship building, and problem-solving collectively helping to restore trust, unity, and organizational reputation. While the study underscores the importance of clear communication in scouting organizations, its limitations in scope and potential subjectivity suggest the need for future research with broader focus and more diverse methods.